IRAD: The use of pesticides in maize culture: Health and environmental impacts on human beings - , Germaine Bienvenue Noukio (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Agriculture in Cameroon is, and remains, the predominant sector of the national economy, both in terms of its contribution to GDP and the training effects on other sectors of activities. Production systems are varied. The following are illustrative: extensive traditional systems, semi intensive traditional systems, enterprise production systems, modern operations. In each of the regions, production systems are characterized by the predominance of one or a few basic cultures, which are associated with secondary cultures. Despite particularly favorable natural conditions, multiples pesticides and agricultural inputs, human beings face serious health problems. In this study, we will analyze the impacts of agricultural inputs used in maize cultivation on human health.